A Basic Study on the Collection of CO Gas Using Direct Air Capture Technology - Young Seok Sim; Dong Sub Lee; Il Gun Park (대한환경공학회지)
As national efforts to achieve carbon neutrality become important, DAC (Direct Air Capture) technology has recently attracted a lot of attention. DAC technology is known to be a technology that can effectively reduce CO2 emitted into the atmosphere, such as transportation and heating. In this study, an experiment was conducted to find out the mechanisms of absorption and adsorption of low atmospheric concentrations CO2. An optimization experiment was conducted to show the maximum removal efficiency during continuous operation by selecting the optimal solvent and adsorbent. In a single absorbent performance experiment in which CO2 gas was introduced at 3L/min with 1wt% of the absorbent, the MEA(MonoEthanolAmine) absorbent was analyzed to have excellent CO2 absorption capacity with 0.34mol-CO2/mol-absorbent. In the case of mixed absorbents, the absorbent mixed with 0.5wt% of AMP (2-Amino-2-Methyl-1-Propanol) in 0.5wt% of MEA showed the best absorption removal rate with 0.52mol-CO2/mol-absorbent in CO2 absorption. In addition, it was analyzed that the CO2 absorption characteristics of the mixed absorbent showed the best absorption performance by mixing AMP with MEA, which showed excellent absorption performance in a single absorbent. In the analysis of low-concentration CO2 adsorption characteristics using adsorbents, zeolite 5A showed the best adsorption performance for CO2 due to a longer adsorption duration than other adsorbents. In particular, in the case of zeolite 5A, it was analyzed that it adsorbed 1.8 times more CO2 than zeolite 13X, 1.2 times more than activated carbon fiber, and 3.5 times more than activated carbon. In the case of zeolite 5A, the specific surface area is larger than that of other adsorbents, and the adsorption performance is relatively excellent because micropores are evenly distributed on the surface.